Contextual factors affecting the integration of community health workers into the health system in Limpopo Province, South Africa. Issue 4 (6th November 2019) - Jobson, Geoffrey; Naidoo, Nireshni; Matlakala, Nthabiseng; Marincowitz, Gert; Railton, Jean; McIntyre, James A; Struthers, Helen E; Peters, Remco P H
Abstract: Background: Community health workers (CHWs) are an essential cadre in the health systems of many low- and middle-income countries. These workers provide a wide variety of services and are key to ongoing processes of task shifting within human immunodeficiency virus programmes in particular. Ward-based outreach teams (WBOTs) are South Africa's latest iteration of the CHW programme and have been introduced as part of the National Department of Health's Primary Health Care Re-engineering programme. Methods: In order to assess the perceived effectiveness of the WBOTs in supporting the ongoing rollout of antiretroviral therapy, tuberculosis care and patient support, we conducted a qualitative investigation focusing on the perceived successes and challenges of the programme among CHWs, community leaders, healthcare workers and community members in the Mopani district, Limpopo province, South Africa. Results: The CHW programme operates across these contexts, each associated with its own set of challenges and opportunities. Conclusions: While these challenges may be interrelated, a contextual analysis provides a useful means of understanding the programme's implementation as part of ongoing decision-making processes.